2011
DOI: 10.3996/012011-jfwm-009
|View full text |Cite
|
Sign up to set email alerts
|

Demography of the San Francisco Gartersnake in Coastal San Mateo County, California

Abstract: The San Francisco gartersnake Thamnophis sirtalis tetrataenia has been federally listed as endangered since 1967, but little demographic information exists for this species. We examined the demography of a San Francisco gartersnake population on approximately 213 ha of California coastal prairie in San Mateo County, California, from 2007 to 2010. The best-supported mark-recapture model indicated annual variation in daily capture probabilities and annual survival rates. Abundance increased throughout the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Neonates were not included in the analysis, therefore births did not affect our population sample. Further, Halstead et al (2011) re ported high annual survival rates for this subspecies (≥0.74, with 95% CL ranging from 0.49 to 0.95), indicating that mortality during our shorter sampling occasions could be assumed minimal. Therefore, Huggins' closed capture models (Huggins 1989(Huggins , 1991 were used to derive estimates of population abundance (N ) and capture (p) and recapture probabilities (c).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Neonates were not included in the analysis, therefore births did not affect our population sample. Further, Halstead et al (2011) re ported high annual survival rates for this subspecies (≥0.74, with 95% CL ranging from 0.49 to 0.95), indicating that mortality during our shorter sampling occasions could be assumed minimal. Therefore, Huggins' closed capture models (Huggins 1989(Huggins , 1991 were used to derive estimates of population abundance (N ) and capture (p) and recapture probabilities (c).…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, we found that young-of-year snakes ranged in size from 152 to ~200 mm, which is in agreement with measurements reported for newborns by Barry (1994) and Larsen (1994). It should be noted that our survey periods did not encompass the expected peak of activity for young-of-year T. s. tetrataenia (based on Halstead et al 2011), and therefore we do not present a reliable maximum size attained for snakes born within the year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations